Haloperidol alters circadian clock gene product expression in the mouse brain. - Coogan, A; Papachatzaki, M; Clemens, C; Baird, A; Donev, R; Joosten, J; Zachariou, V; Thome, J (2011)
OBJECTIVES: Circadian rhythms are patterns in behavioural and physiological measures that recur on a daily basis and are driven by an endogenous circadian timekeeping system whose molecular machinery consists of a number of clock genes. The typical anti-psychotic haloperidol has previously been shown to induce significant deficiencies in circadian timing in patients. In this study we examined the impact of haloperidol treatment on molecular components of the circadian clock in the mouse brain. METHODS: We examined how haloperidol treatment, either acute (both at day and night) or chronically over 14 days, alters the expression of three clock gene protein products (PER1, PER2, BMAL1) across the mouse brain by means of immunohistochemistry. RESULTS: Chronic haloperidol treatment significantly decreases the expression levels of PER1 in a number of brain areas, including the hippocampus, the prefrontal and cingulate cerebral cortex and the paraventricular nucleus of the hypothalamus. PER2 expression was only altered in the dentate gyrus and the CA3, and BMAL1 expression was only altered in the paraventricular nucleus of the hypothalamus. CONCLUSION: These data indicate that haloperidol has the potential to alter circadian rhythms via modulation of circadian clock gene expression.